The KB e-Depot: Building and Managing a Safe Place for e-Journals - Ras, Marcel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
This article describes the policies behind the e-Depot of the National Library of the Netherlands and the experience of running an operational digital archive, focussing on the lessons learned after six years of operations in terms of collections, technology, organisation and staff. It concludes with an international collaborative perspective on digital preservation.